Evaluación del rendimiento del cultivo de chía (Salvia hispánica L.), con la aplicación de fuentes de abono químico y orgánico - Navarrete Molina, Carlos Manuel (2017)
VIII. SUMMARY This research study crop yield chia (Salvia hispanica L), sources with the application of chemical and organic fertilizer in the area belonging of the Carlizamá Espejo, Carchi province, located in the coordinates, 0 ° 34`22 61 "north latitude and 78 ° 0`1.31" 0 west longitude, altitude of 2,799 mbls. The aim of the research was to assess the crop yield chia subject to the application of chemical and organic fertilizer application and identify the best response and economically analyze treatments. Design Randomized Complete Block (DRCB) was used with 8 treatments; Eco Abonaza, Humus, Gallinaza, 15-15-15, 15-15-15 + Eco Abonaza, Humus + 15-15-15 + 15-15-15 Gallinaza and Without application with three repetitions, giving a total of 24 units experimental. The total area was 533 m2, 12 m2 plots with a total net area of 5.04 m2. The variables evaluated were; germination percentage, plant height, number of nodes, days to flowering, days to harvest, root size, root weight, yield for experimental unit and weight for volume. All variables were subjected to analysis of variance and to determine the statistical difference between treatment means the Tukey test was conducted at 5%. The results obtained in the investigation determined that the cultivation of chia responded positively to the implementation of Eco Abonaza + 15-15-15 presented good percentage of germination, plant height, number of nodes, in days to flowering, root size, higher yield for experimental unit and Humus + 15-15-15 application, which also showed significant values in percentage of germination, plant height, yield per experimental unit and weight for volume, in both cases had the highest economic profit for hectare.